(untitled) - Connor, John T. (Hoboken, N.J., 2008)
Over the last fifteen years, Russia has become a larger part of the global economy—and in the years ahead, it will continue to grow in prominence. If you want to improve your investment endeavors in this market, you must first understand how it operates. With Out of the Red as your guide, you’ll become familiar with all the opportunities this country has to offer and learn how to make the most informed investing decision within this emerging arena
Keywords: Investments,Capitalism,Đầu tư,Quỹ đầu tư; Russia (Federation),Russia (Federation),Liên Bang Nga,Liên Bang Nga